Prediction of relapse among individuals undergoing methadone maintenance therapy in Johor Bahru Healath district - Mohmad, Faradia; Ismail, Suriani; Abdul Manaf, Rosliza (Universiti Putra Malaysia Press, 2022)
Increase in the number of opioids seized in the recent year may indicate increased opioid use in Malaysia. In counteracting opioid abuse, Methadone Maintenance Therapy (MMT) was introduced in Malaysia but relapse following MMT has become an important issue. This study aimed to determine the prevalence and patient factors that served as predictors of opioid relapse among MMT patients. Method: A cross-sectional study involving 159 MMT patients who have reached dose stabilization (eight weeks at a constant dose of methadone) was conducted in Johor Bahru Health District. The dependent variable was opioid relapse, while the independent variables include socio-demographic characteristics, MMT history, crime history, cognitive and interpersonal factors, and social-environment influence. Face-to-face interviews using structured questionnaires and secondary data collection using data collection sheets were done. Multiple logistic regression was used to determine the predictors. Significant level set at alpha less than 5%. Result: The response rate was 86.9% with majority of them were Malay, male, and Muslim. The prevalence of opioid relapse was 11.9%. Those who were non-polydrug users (AOR=3.701, 95%CI=1.182, 11.587, p=0.025), classified as having moderate (AOR=5.869, 95%CI=1.524, 22.595, p=0.010) and high (AOR=5.952, 95%CI=1.000, 35.445, p=0.050) relapse risk response after given hypothetical situation whether respondent been offered drug or not, were more likely to have relapsed. Respondents with higher cognitive and behavioral problem-solving response scores were less likely to have relapsed (AOR=0.949, 95%CI=0.909, 0.991, p=0.008). Conclusion: About 1 in 5 MMT clients had relapsed after they reach dose stabilization. The predictors of opioid relapse were non-polydrug users, having moderate to high relapse risk, and cognitive and behavioral problem-solving responses.